Bulworth [videorecording (DVD)] - Beatty, Warren, 1937-; Berry, Halle; Sorvino, Paul; Warden, Jack; Cheadle, Don; Platt, Oliver; Washington, Isaiah (20th Century Fox Home Entertainment, 1999)
Believing his career is over, Senator Jay Bulworth takes out an enormous insurance policy and a contract on his own life. His impending death fills him with an outrageous desire to break the rules and tell it like it is.